Barbigerone attenuates 3-nitropropionic acid-induced Huntington’s disease-like neuropathology in rats via antioxidant, anti-inflammatory, and neuroprotective mechanisms - Sattam Khulaif Alenezi (Scientific Reports)
Abstract Huntington’s Disease (HD), a neurodegenerative disease characterized by motor and cognitive impairments, arises from genetic mutations causing protein aggregation within the brain. The 3-Nitropropionic acid (3-NPA) rat model mimics key features of HD. This study explored the therapeutic efficacy of barbigerone, a compound with antioxidant and anti-inflammatory properties, in ameliorating 3-NPA-induced neurodegeneration and cognitive deficits in rats. Male Wistar rats were randomized into four groups: a normal control group, a 3-NPA control group, and two groups treated with different doses of barbigerone along with 3-NPA. Behavioral test, biochemical assays, and histopathological examinations were performed. Barbigerone significantly (P < 0.0001) restored motor coordination, grip strength, and mobility compared to 3-NPA-induced HD rats. Barbigerone concomitantly reduced oxidative stress by lowering malondialdehyde (MDA) and nitric oxide (NO) levels, while enhancing antioxidant enzymes such as glutathione (GSH), superoxide dismutase (SOD), and catalase (CAT). Furthermore, treatment modulated the pro-inflammatory cytokines, suggesting a reduction in neuroinflammation. Barbigerone significantly (P < 0.0001) impacted changes in acetylcholinesterase (AChE) activity and modulated levels of key neurotransmitters, such as acetylcholine (ACh), norepinephrine (NE), serotonin (5-HT), gamma-aminobutyric acid (GABA), dopamine (DA), and glutamate (GLU). Additionally, barbigerone effectively attenuated the 3-NPA-induced elevation of caspase-3 and caspase-9, while upregulating brain-derived neurotrophic factor (BDNF), which is crucial for neuronal survival and cognitive function. Histopathological examination revealed that barbigerone significantly restored the altered striatal architecture, indicating a protective effect against neurodegeneration. Barbigerone exhibits potential as a therapeutic choice for HD, offering the possibility of alleviating motor impairments, oxidative stress, inflammation, and cognitive dysfunction.